Vibrational and electronic circular dichroism studies on the axially chiral pyridine-N-oxide: trans-2, 6-di-ortho-tolyl-3, 4, 5-trimethylpyridine-N-oxide. Issue 18 (15th October 2015) - Teodorescu, Florina; Nica, Simona; Uncuta, Cornelia; Bartha, Emeric; Filip, Petru Ivan; Vanthuyne, Nicolas; Roussel, Christian; Mándi, Attila; Tóth, László; Kurtán, Tibor; Naubron, Jean-Valère; Man, Isabela-Costinela
Graphical abstract: Abstract: The absolute configuration of the resolved axially chiral pyridine- N -oxide derivative, (±)- trans -2, 6-di- ortho -tolyl-3, 4, 5-trimethylpyridine- N -oxide, has been determined by VCD and ECD analyses supported by TD-DFT calculations carried out at different levels of theory. DFT calculations confirmed that in spite of the two biaryl axes, the compound is conformationally less flexible and the major conformer is stabilized by two weak hydrogen bonds formed between the hydrogen of the methyl group of the tolyl moieties and the nitroxide oxygen. The experimental VCD spectra of this compound and the previously studied (±)-2, 6-di-sec-butyl-4-methylpyridine-N-oxide with two stereogenic centers were compared in the frequency range 1200–1300 cm −1 . A (+, −, +)/(−, +, −) pattern of bands was observed in both cases. By replacing the sec -butyl moieties with tolyl ones, the VCD peaks shifted toward higher frequencies and the intensities were increased. Abstract : (a R, a R )- trans -2, 6-di- ortho -tolyl-3, 4, 5-trimethylpyridine- N -oxide: C22 H23 NO [ α ]25 589 = −171.6 ( c 1, CHCl3 ) Source of chirality: VCD spectroscopy and DFT calculations Absolute configuration: (a R, a R )